Exploring Social (Non-working) Behavior in Guide Dogs from the Perspective of Guide Dog Owners. (3rd September 2018) - York, Sarah; Whiteside, Helen
ABSTRACT: The guide dog partnership begins at the point of matching, when careful assessment of a trained guide dog and an understanding of the functional needs and expectations of the prospective owner are considered alongside each other. Guide Dogs UK invest much time and resources to the process of matching a client with a dog in order to fulfil client expectations and create a lasting partnership. This study explores: (1) the meaning and importance of social (non-working) behavior to guide dog owners; (2) how firsthand experience and knowledge shape individual owner expectations for behavior; and (3) how, and in what ways, social behavior impacts the guide dog partnership. The focus group method was used to collect qualitative data from a total of 11 participants. The data were analyzed using a thematic analysis procedure which identified six overarching themes: "social behavior to me means, " internal and external factors influencing social behavior, training and matching, socially desirable and undesirable behaviors, maintaining and managing social behavior, and practical and emotional issues. Findings show that social behavior is as important as guiding skills and mobility for guide dog owners, and behavioral compatibility is held to be crucial in a successful partnership. Participants put an emphasis on consistency of behavior in social settings, while recognizing that a guide dog's non-working behavior is subject to multifarious internal and external influences. The findings of this study indicate an opportunity for Guide Dogs UK, and similar assistance dog organizations, to observe fully the importance of social behavior and, in response, place even greater emphasis on lifestyle and behavioral compatibility when training dogs and matching them with clients.